CRUZ HERNÁNDEZ, M., LOMBA FUENTES ,J., PUIG MONTADA, J. & RAMÓN GUERRERO, R.: Filosofía medieval árabe en España. - Segovia, Carlos A. (Anales del Seminario de Historia de la Filosofía, 2001)
Sin resumen